Analisis Makna pada Bento sebagai Komunikasi Nonverbal dalam Film Bento Harassment Melalui Teori Semiotika Roland Barthes - Rahma Putri, Ru'yatun Nazma; Santoso, Budi (KIRYOKU, 2025)
This research analyzes bento inscriptions as a form of nonverbal communication in the film Bento Harassment (今日も嫌がらせ弁当) through Roland Barthes semiotic theory. Employing a qualitative descriptive method, it explores how denotation, connotation, and myth are reflected in bento messages, revealing emotions, cultural values, and the mother-daughter relationship dynamics. At the denotative level, the bento is a literal meal; at the connotative level, it conveys the mother's affection, frustration, and moral lessons. Mythologically, the bento symbolizes Japanese cultural values, such as hard work and indirect family communication, illustrating how food expresses love and care. This study contributes to semiotics in visual culture by demonstrating how everyday objects like bento serve as symbolic tools for conveying meaning beyond verbal communication.